2018
DOI: 10.1039/c8ob02094a
|View full text |Cite
|
Sign up to set email alerts
|

New Friedel–Crafts strategy for preparing 3-acylindoles

Abstract: A new Friedel–Crafts acylation generates diverse high-biological value 3-acylindoles, and forms a new C–C bond under transition-metal-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In 2018, Liang et al introduced a Friedel-Crafts acylation of indoles 27 using tertiary amides 28 as acylated reagent in the presence of Tf 2 O as activator, Cs 2 CO 3 as base and CsF as additive in toluene at 70°C (Scheme 6). [15] Under these conditions, a wide range of amides 28 containing alkyl, branched alky, cycloalkyl and aryl chains (R 4 ) and N-substituted amides (R 5 , R 6 ) reacted with N-protected and non-N-protected indoles 27 to produce the corresponding 3-acylindoles 30 with high biological potency in low to high yields (28-91 %). The proposed mechanism confirmed by 13 CNMR indicated that the quickly activation of amides 28 by Tf 2 O and then attacked by indoles produced the iminium triflates 29 as key intermediates.…”
Section: Dr Zahra Tashrifi Was Born In 1984 Inmentioning
confidence: 99%
“…In 2018, Liang et al introduced a Friedel-Crafts acylation of indoles 27 using tertiary amides 28 as acylated reagent in the presence of Tf 2 O as activator, Cs 2 CO 3 as base and CsF as additive in toluene at 70°C (Scheme 6). [15] Under these conditions, a wide range of amides 28 containing alkyl, branched alky, cycloalkyl and aryl chains (R 4 ) and N-substituted amides (R 5 , R 6 ) reacted with N-protected and non-N-protected indoles 27 to produce the corresponding 3-acylindoles 30 with high biological potency in low to high yields (28-91 %). The proposed mechanism confirmed by 13 CNMR indicated that the quickly activation of amides 28 by Tf 2 O and then attacked by indoles produced the iminium triflates 29 as key intermediates.…”
Section: Dr Zahra Tashrifi Was Born In 1984 Inmentioning
confidence: 99%
“…[51] In 2018, Liang group reported the synthesis of 3-acylindoles 101 by transition-metal-free method by Friedel-Crafts acylation of indoles 99 using amides 100 as an acyl source via CÀ N bond cleavage in the presence of triflic anhydride (Scheme 22). [52] In 2020, Matsuo, reported the deaminative acylation of activated aliphatic amines (Katritzky salts) 102 using aromatic amides 92 via CÀ N bond activation in the presence of Ni-catalyst. Besides, this protocol is applicable for late-stage functionalization, various Katritzky salts bearing natural products and pharmaceutical intermediates were cross-coupled with amide to yield corresponding acylated products 103 (Scheme 23).…”
Section: Cyclobutenonesmentioning
confidence: 99%
“…Oxidized alkylarenes are extensively used in the transformations in organic chemistry, 1 preparation of aromatic precursors in pharmaceutical industry, 2 commercial production of oxygen‐containing compounds, 3 development of advanced materials, 4 as well as key intermediates upon the synthesis of fine chemicals 5 . Consequently, synthetic approaches of oxidized alkylarenes have been actively developed including esterification, 6 Friedel‐Crafts acylation, 7 and catalysis 8 . Nevertheless, an excess amount of oxidizing reagents and harsh conditions were required in the conventional alkylarene oxidations 9 .…”
Section: Introductionmentioning
confidence: 99%